2022
DOI: 10.3390/genes13071218
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic and Genetic Features of Bardet Biedl Syndrome in a German Cohort

Abstract: The aim of this study was to characterize the ophthalmic and genetic features of Bardet Biedl (BBS) syndrome in a cohort of patients from a German specialized ophthalmic care center. Sixty-one patients, aged 5–56 years, underwent a detailed ophthalmic examination including visual acuity and color vision testing, electroretinography (ERG), visually evoked potential recording (VEP), fundus examination, and spectral domain optical coherence tomography (SD-OCT). Adaptive optics flood illumination ophthalmoscopy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…We observed BBS10 as the most frequently mutated gene ( N = 16) and p.C91Lfs*95 was seen in three probands (Table 2). BBS1, BBS2, ARL6, BBS5, MKKS, BBS7 , and BBS12 genes were seen in >5% of our study cohort which is comparable with the world wide reports except for BBS1 and BBS12 genes 26–28 . Variations in BBS1 gene were frequently reported worldwide (23%), 2 while only 7.4% of our patients harbored the same and the widely reported missense variant p.M390R was not seen in our probands.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed BBS10 as the most frequently mutated gene ( N = 16) and p.C91Lfs*95 was seen in three probands (Table 2). BBS1, BBS2, ARL6, BBS5, MKKS, BBS7 , and BBS12 genes were seen in >5% of our study cohort which is comparable with the world wide reports except for BBS1 and BBS12 genes 26–28 . Variations in BBS1 gene were frequently reported worldwide (23%), 2 while only 7.4% of our patients harbored the same and the widely reported missense variant p.M390R was not seen in our probands.…”
Section: Discussionsupporting
confidence: 88%
“…BBS1, BBS2, ARL6, BBS5, MKKS, BBS7, and BBS12 genes were seen in >5% of our study cohort which is comparable with the world wide reports except for BBS1 and BBS12 genes. [26][27][28] African regions 23 while we observed BBS4 variations in 2.7% and BBS5 variations in 4.6% of our patients. Frequency of MKKS and BBS7 variations were quite similar to the frequencies reported in other populations (MKKS-5.4%, 31 BBS7-1.5%-3%).…”
Section: Molecular Genetic Spectrum In Bbs Patientssupporting
confidence: 47%
“…Twelve clinical studies reported morphofunctional characteristics of the IRDs [ 8 , 14 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Patients were divided into five groups according to their IRD.…”
Section: Morphofunctional Finding In Irdmentioning
confidence: 99%
“…The third study, by Fadi Nasser et al [ 52 ], was characterized by OCT and ERG, including a cohort of sixty-one German patients aged between 5 and 56 years with 51 different biallelic mutations. OCT images of all 20 patients with BBS10 showed atrophy of the photoreceptor layer and loss of photoreceptor cells, mostly together with wrinkles of the inner limiting membrane.…”
Section: Morphofunctional Finding In Irdmentioning
confidence: 99%
“…To understand whether the clinical manifestations of BBS are consistent across patients worldwide, we compared the phenotypes of our Chinese cohort with those of the three cohorts from other countries: Spain, Germany, and India [16,17,18] (Table 2). The average age in the Chinese cohort was younger than that in the Spanish and German cohorts, while older than that in the Indian cohort.…”
Section: Phenotypic Comparison Between Our Chinese Cohort and Cohorts...mentioning
confidence: 99%